Levels of Small Extracellular Vesicles Containing Herg-1 and hsp47 as Potential Biomarkers for Cardiovascular Diseases - Iturriaga-Jofre, A (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The diagnosis of cardiovascular disease (CVD) is still limited. Therefore, this study demonstrates the presence of human ether-a-go-go-related gene 1 (hERG1) and heat shock protein 47 (Hsp47) on the surface of small extracellular vesicles (sEVs) in human peripheral blood and their association with CVD. In this research, 20 individuals with heart failure and 26 participants subjected to cardiac stress tests were enrolled. The associations between hERG1 and/or Hsp47 in sEVs and CVD were established using Western blot, flow cytometry, electron microscopy, ELISA, and nanoparticle tracking analysis. The results show that hERG1 and Hsp47 were present in sEV membranes, extravesicularly exposing the sequences 430AFLLKETEEGPPATE445 for hERG1 and 169ALQSINEWAAQTT- DGKLPEVTKDVERTD196 for Hsp47. In addition, upon exposure to hypoxia, rat primary cardiomyocytes released sEVs into the media, and human cardiomyocytes in culture also released sEVs containing hERG1 (EV-hERG1) and/or Hsp47 (EV-Hsp47). Moreover, the levels of sEVs increased in the blood when cardiac ischemia was induced during the stress test, as well as the concentrations of EV-hERG1 and EV-Hsp47. Additionally, the plasma levels of EV-hERG1 and EV-Hsp47 decreased in patients with decompensated heart failure (DHF). Our data provide the first evidence that hERG1 and Hsp47 are present in the membranes of sEVs derived from the human cardiomyocyte cell line, and also in those isolated from human peripheral blood. Total sEVs, EV-hERG1, and EV-Hsp47 may be explored as biomarkers for heart diseases such as heart failure and cardiac ischemia. © 2024 by the authors.